More than a safety net: Ethiopia’s flagship public works program increases tree cover - Hirvonen, Kalle; Machado, Elia A.; Simons, Andrew M.; Taraz, Vis (Elsevier, 2022)
More than one billion people worldwide receive cash or in-kind transfers from social protection programs. In low-income countries, these transfers are often conditioned on participation in labor-intensive public works to rehabilitate local infrastructure or natural resources. Despite their popularity, the environmental impacts of public works programs remain largely undocumented. We quantify the impact on tree cover of Ethiopia’s Productive Safety Net Program (PSNP), one of the world’s largest and longest-running public works programs, using satellite-based data of tree cover combined with difference-in-differences and inverse probability treatment weighting methodologies. We find that the PSNP increased tree cover by 3.8% between 2005 and 2019, with larger increases in less densely populated areas and on steep-sloped terrain. As increasing tree cover is considered an important strategy to mitigate global warming, our results suggest a win–win potential for social safety net programs with an environmental component.